Impact of Organizational Culture on Employee Engagement and Employee Performance: A Stimuli-Organism-Response Approach - Halid Hasan; Endang Siti Astuti; Tri Wulida Afrianty; Mohammad Iqbal (Wacana Journal of Social and Humanity Studies, 2020)
This study examines the impact of organizational culture on employee engagement and employee performance. Within the organization, organizational culture plays an important role in building employee engagement, and ultimately in Employee Performance. The causality study is used to analyze the influence of the variables involved in this study. This type of research is quantitative descriptive with multi-stage sampling. The data was collected by using a questionnaire to 251 respondents from 9 branch offices of government banks, Malang regional offices. Data were analyzed using smartPLS (Partial Least Square) which includes measurement models and hypothesis testing. The findings indicate that organizational culture has a direct and significant positive influence on employee engagement and employee performance. Besides, organizational culture also has a significant indirect positive effect on employee performance through employee engagement. Bank managers, practitioners, and research institutions can use the findings to enhance organizational culture, employee engagement to drive employee performance.